Cubic Maiorana–McFarland bent functions with no affine derivative. Issue 1 (2nd January 2017) - Mandal, Bimal; Gangopadhyay, Sugata; Stănică, Pantelimon
ABSTRACT: A class of cubic Maiorana–McFarland ( ) bent functions having no affine derivative was constructed by Canteaut and Charpin [ Decomposing bent functions, IEEE Trans. Inform. Theory 49(8) (2003), pp. 2004–2019], thereby solving an open problem posed by Hou [ Cubic bent functions, Discrete Math. 189 (1998), pp. 149–161]. The goal of the paper is twofold: we construct two classes of cubic bent functions with no affine derivative and show their mutual affine inequivalence.